Trace and Rare Earth Elements Compositional Change on Andesite Alteration in Kaligesing, Purworejo - Joko Subandrio; Ronaldo Irzon (Pusat Survei Geologi, 2020)
The change of chemical composition because of hydrothermal alteration process is related to the modification on mineralogy and elements mobility. Different alteration conditions could lead to dissimilar geochemical character. This study aims to discuss the alteration effect on trace and rare earth elements composition of an andesite outcrop with hydrothermal alteration in Kaligesing, Purworejo, Central Java Province. Microscopic analysis at Central for Geological Survey was applied to determine the modal mineral composition of the selected samples whilst trace and rare earth elements abundances was measured using Inductively Coupled Plasma – Mass Spectrometry. Plagioclase is the major phenocryst embedded in the fine-grained feldspar and glass groundmass of relatively fresh andesite. On the other hand, sericite, chlorite, epidote, and iron oxide are detected in the altered rock. The more Sr and Rb compositions on unaltered sample exhibit their common existence in plagioclase. The bigger Rb/Sr and the lower Ba/Sr ratios inward to the center of alteration might indicate the more degree of K-bearing mineral formation than Ca-rich mineral alteration. The Ba/Zr escalation and Zr/Y reduction from relatively fresh rock through to the vein of the studied samples are parallel to the previous investigation about andesite alteration. Chondrite-normalized rare-earth elements (REE) pattern of unaltered, altered, and vein samples depicts similar patterns: strong enrichment of Low REE, positive Eu anomaly, and relatively flat high REE. The decrease of Eu anomaly may reflect the reduction of plagioclase modal composition because of alteration and might indicate a reductive alteration state.Keywords: Alteration, andesite, geochemistry, trace and rare earth elements.